(untitled) (Bangladesh Journal of Obstetrics & Gynaecology, 2016)
Objective (s): The aim of the study was to assess ovarian reserve (OR) of patients with endometrioma and to explore the differences of ovarian reserve in age matched group of infertile patients without endometrioma. Materials and methods: This prospective analytic study was done in Infertility Care and Research Center, between January 2013 and December 2015 to assess the ovarian reserve of patients with endometrioma. During this period 105 patients of endometriosis with endometrioma were selected for study. Selection criteria were: no history of previous surgery, <36 years of age, no history of endocrine problems, no history of recent medical treatment for this condition within 6 months and no history of irregular menstruation. For ovarian reserve testing we assessed serum FSH, E2 and AMH. Patient of same age group who had no emdometrioma, no history of any surgery, no menstrual irregularity, endocrine disorder or any other medical diseases were taken as control to compare the ovarian reserve between these two groups. For control group also we did the same tests. Data was analyzed by SPSS package. One-way ANOVA test was done for test of significance. A p-value of <0.05 was considered as significant. Results: There was no difference in characteristics of patients of both groups regarding age, type of infertility and duration of infertility. Size of the endometriotic cysts were variable and average diameter of cyst was 6.2 ±2.32 cm. Most (58.10%) of the cysts were unilateral. There is a significant difference of FSH and AMH level between the groups. FSH of endometrioma and non-endometrioma group was 7.9 ±1.17 and 7.1 ±1.05 mIU/mL respectively with a p value of 0.029. Similar difference was present in AMH level, which was 2.42 ±.63 and 2.98 ±.88 ng/ mL in endometrioma and non-endometrioma group respectively with a p value of 0.020. Conclusion: This small study shows a reduced ovarian reserve in patients with endometrioma in comparison to patients of same parameters without endometrioma. It suggests that there is an association of presence of ovarian endometrioma and reduced ovarian reserve Bangladesh J Obstet Gynaecol, 2015; Vol. 30(2) : 98-104